2012
DOI: 10.1158/1541-7786.mcr-11-0524
|View full text |Cite
|
Sign up to set email alerts
|

STEAP1 Is Associated with the Invasive and Oxidative Stress Phenotype of Ewing Tumors

Abstract: Ewing tumors comprise the second most common type of bone-associated cancer in children and are characterized by oncogenic EWS/FLI1 fusion proteins and early metastasis. Compelling evidence suggests that elevated levels of intracellular oxidative stress contribute to enhanced aggressiveness of numerous cancers, possibly including Ewing tumors. Using comprehensive microarray analyses and RNA interference, we identified the six-transmembrane epithelial antigen of the prostate 1 (STEAP1)-a membrane-bound mesenchy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
132
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 47 publications
10
132
0
Order By: Relevance
“…As shown in Figure 5C, A673 and SK-N-MC HOXD10, HOXD11 and HOXD13 shRNA infectants revealed a significant contribution of at least HOXD11 and HOXD13 to in vitro invasiveness. Recent results of our laboratory already indicated a strong contribution of MMP1 to invasion and metastasis of ES and its possible induction via several, presumably independent pathways [5,38,39]. Figure S5B) signifying that the reduced invasive potential of HOXD11 or HOXD13 and probably HOXD10 silenced ES cells may be mediated at least in part via MMP1.…”
Section: Hoxd Genes Promote Es Growth and Invasivenessmentioning
confidence: 77%
“…As shown in Figure 5C, A673 and SK-N-MC HOXD10, HOXD11 and HOXD13 shRNA infectants revealed a significant contribution of at least HOXD11 and HOXD13 to in vitro invasiveness. Recent results of our laboratory already indicated a strong contribution of MMP1 to invasion and metastasis of ES and its possible induction via several, presumably independent pathways [5,38,39]. Figure S5B) signifying that the reduced invasive potential of HOXD11 or HOXD13 and probably HOXD10 silenced ES cells may be mediated at least in part via MMP1.…”
Section: Hoxd Genes Promote Es Growth and Invasivenessmentioning
confidence: 77%
“…18 STEAP proteins are homologs of NADPH-oxidases (NOX), involved in cellular ROS metabolism and frequently overexpressed in cancers. We demonstrated that STEAP1 is induced by EWS-FLI1 and that its expression promotes proliferation, invasiveness, anchorage-independent colony formation, tumorigenicity and metastasis of ES cells, 19 as well as impacting on patient survival. 35 Apart from minor expression in prostate and urothelium, STEAP1 is only weakly expressed in normal tissues.…”
Section: Discussionmentioning
confidence: 91%
“…19 Apart from minor expression in prostate and urothelium, STEAP1 is only weakly expressed in normal tissues (Figs. S1 and S2A).…”
Section: Steap1mentioning
confidence: 99%
See 2 more Smart Citations